Human Papillomavirus and Related Diseases From Bench to Bedside - A Diagnostic and Preventive Perspective - Vanden Broeck, Davy (IntechOpen, 2013)
Cervical cancer is the second most prevalent cancer among women worldwide, and infection with Human Papilloma Virus (HPV) has been identified as the causal agent for this condition. The natural history of cervical cancer is characterized by slow disease progression, rendering the condition in essence preventable and even treatable when diagnosed in early stages. Pap smear and the recently introduced prophylactic vaccines are the most prominent prevention options, but despite the availability of these primary and secondary screening tools, the global burden of disease is unfortunately still very high This book will focus on the clinical and diagnostic aspects of HPV and related disease, highlighting the latest developments in this field.